Optimizing Open Green Space on Urban Campuses Through the Case of UI Salemba Campus: A Step Towards Improved Green Metric Ranking - Wurianturi, Indrajati; Sari Hasibuan, Hayati; Suganda, Emirhadi (Nakhara : Journal of Environmental Design and Planning, 2022)
Universities are trying to make their campuses sustainable. One of the tools used to evaluate the level of campus sustainability is UI Green Metric World University Rank (UIGMWUR), which focuses on sustainable efforts implemented by universities. It has become clear, however, that it is difficult for urban campuses to obtain a good ranking under the UIGMWUR framework due to the limited amount of open green space in dense city areas. Therefore, one possible strategy involves optimizing the existing open green space. This research was conducted to determine some possible solutions through the use of observation and a Likert scale questionnaire. The initial result showed that the building coverage area exceeds the government standard, and that most of the people on campus have a negative perception of the open green space that currently exists. The community prefers green space that offers privacy, with big canopy trees and natural elements. The study combined these preferences with a biophilic design pattern to generate a design proposal. It was concluded that there is a need to optimize the open green space in urban campuses based on four strategies: building vertical gardens, renovating the existing open green spaces, optimizing the buildings, and constructing vertical parking facilities.